Strengthening regional institutional capacity for climate information services in West Africa and the Sahel: Stocktaking AICRRA contributions - Assoumana, Boubacar Toukal; Ali, Abdou; Mohamed, Hamatan; Houngnibo, Mandela C. M.; Soumana, Djibo; Segnon, Alcade Christel; Zougmore, Robert Bellarmin (2025)
AICCRA’s targeted activities have catalyzed transformative changes in AGRHYMET’s technical and institutional capacities. With AICCRA’s support, AGRHYMET significantly strengthened its expertise in advanced climate and hydrology forecasting systems. AICCRA project accelerated the transition from consensus-based to objective forecasts in West Africa and the Sahel region, enhancing accuracy, transability, and reproducibility. This transition was officially endorsed by the Directors of all 17 National Meteorological and Hydrological Services (NMHSs) of the region. AICCRA also supported the intense capacity building of SMHNs allowed the establishment of a regional community of practice around the new generation of hydro-climate services. In terms of infrastructure, AICCRA contributed to strengthening AGRHYMET’s computing capacity with the acquisition of high-performance servers (Titan S600 GPUs) that facilitates the optimal operations of the Watch Room. AICCRA gender experience impacted AGRHYMET with a more proactive inclusion and gender-sensitive approach in capacity building and climate services delivery. AICCRA promoted a culture of systematic valorization of project outcomes through development of knowledge products. Several knowledge products developed by AGRHYMET have enhanced their scientific visibility. AICCRA’s overall support contributed to fast-tracking the process of AGRHYMET’s accreditation by WMO. In terms of project management, the results-oriented approach of the AICCRA project is an experience to be promoted for other initiatives.